Diaspora, gender and narrative journeys : Italian migrant women in Ireland - De Tona, Carla (Trinity College (Dublin, Ireland). Department of Sociology, 2008)
Diaspora, Gender And Narrative Journeys: Italian Migrant Women In Ireland. This study concerns Italian migrant women in Ireland, who are the most invisible subjects of a forgotten yet ‘exceptional’ history of migration. It focuses on migrants’ sense of belonging and affiliation, conceptualising the Italian women’s condition of being in migration as that of a ‘double diaspora’ (doubly invisible and removed, as migrant and as women but also as actors of a two-tiered sociality). The analysis is based on open-ended and unstructured interviews conducted with 29 Italian women of first, second and third-generation migrants and on document analysis, focusing on existing representations of Italian migrants in Ireland and on the politicisation of diasporic discourses in Italy. This study holds women’s personal narratives as informative of gendered meanings of migration, and as performative practices, which allow shifting gender norms to sustain the fluidity of diasporic identities. The analysis demonstrates that in diaspora, women's narrative practices function as a social strategy to create collective (gender and diasporic) boundaries, which are both stable and shifting. Women’s narratives allow the women to forge new gender roles within their families and groups and to find a place in their diasporic destinations, supporting their migration process, providing them company and containing their isolation.
Keywords: Sociology, Ph.D.; Ph.D. Trinity College Dublin